2004
DOI: 10.1021/cm049836h
|View full text |Cite
|
Sign up to set email alerts
|

MOCVD of Bismuth Oxides:  Transport Properties and Deposition Mechanisms of the Bi(C6H5)3 Precursor

Abstract: Deposition processes of bismuth oxides have been investigated using the Bi(C 6 H 5 ) 3 precursor. The role of the MOCVD parameters has been evaluated through the study of both the precursor sublimation and the entire CVD process depending on the temperature and the reactor environment. In the 350-450 °C range, Bi 2 O 3 deposition follows a heterogeneous pathway leading to the dissociation of Bi-phenyl bonds. O 2 plays a determining role in both the precursor decomposition and Bi 2 O 3 growth. Above 450 °C, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
33
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 55 publications
2
33
0
Order By: Relevance
“…13 Similarly [Bi(o-tol) 3 ] and [Bi(ptol) 3 ] have been shown to be useful bismuth precursors for growth of bismuth oxide films. 14 However, the high thermal stability of these precursors requires high deposition temperatures and carbon contamination can be problematic.…”
mentioning
confidence: 99%
“…13 Similarly [Bi(o-tol) 3 ] and [Bi(ptol) 3 ] have been shown to be useful bismuth precursors for growth of bismuth oxide films. 14 However, the high thermal stability of these precursors requires high deposition temperatures and carbon contamination can be problematic.…”
mentioning
confidence: 99%
“…[1] These properties make Bi 2 O 3 films well suited for many applications such as microelectronics, [2] sensor technology, [3] optical coatings, [4] and ceramic glass manufacturing. [5] Various precursors have been employed to synthesize Bi 2 O 3 films by CVD, including bismuth halides and bismuth triphenyl Bi(Ph) 3 .…”
mentioning
confidence: 99%
“…[5] Various precursors have been employed to synthesize Bi 2 O 3 films by CVD, including bismuth halides and bismuth triphenyl Bi(Ph) 3 . [1,2,4,[6][7][8][9][10][11] Halides are known to be toxic and corrosive. Bi(Ph) 3 is safer and offers remarkable advantages in terms of thermal stability and clean sublimation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that main phase of the nanorods synthesized in the present work is the tetragonal β-Bi 2 O 3 structure, whereas that in Takeyama et al's work the monoclinic α-Bi 2 O 3 structure. Bedoya et al previously reported the dependence of crystalline phase on the deposition temperature [22], revealing that the monoclinic α-Bi 2 O 3 structure is favored at higher temperature. We have fabricated the nanorods with tetragonal β-Bi 2 O 3 structure at a relatively low temperature, which is a metastable phase and will exhibit a promising ionic conductivity by the deliberate doping [23,24].…”
Section: Resultsmentioning
confidence: 93%